Leadership Education in the Digital Age - Andriani, Rini; Hasyim, Hasyim; Dewi, Rahma; Tantri, Afri; Nurkadri, Nurkadri (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
Leaders or leaders of an educational institution as people who are used to deciding what is right or most appropriate in certain situations, especially in the education policy itself. Of course, in the current era of the Industrial Revolution 4.0, policy is all about elements and values. The match is in the section itself. From individuals to world interests, their infrastructure must be properly managed. Education is actually a means to advance human civilization, plays an open role in this Industrial Revolution era, and must comply with aims and objectives without being constrained by regional interests. To prevent this very rapid development from being hampered or misdirected, we really need a very optimal role. New education policies need to be developed easily and quickly, but still put humanity first. This is of course the realm of education.